Hydroxyapatite Coatings on Titanium Alloy TNTZ using Electrophoretic Deposition. (August 2019) - Gunawarman,; Nuswantoro, N F; Juliadmi, D; Fajri, H; Budiman, A; Tjong, D H; Manjas, M
Abstract: TNTZ is a β-type titanium alloy that designed for orthopedic implant application. This material has superiority in mechanical properties such as high strength to work on load bearing or dynamic bearing, elasticity that is close to the human bone, contained non-toxic materials, and biocompatible. However, the inertness of titanium made this material still have no bioactivity, so that it cannot trigger the bone tissue to grow faster and produce optimum osseointegration. Hydroxyapatite (HA) has chosen as the coating material for TNTZ since the biocompatibility and bioactivity of this ceramic material. So that, by combining mechanical properties of TNTZ and bioactivity of HA it can be expected that better orthopedic implant would be produced. Electrophoretic Deposition (EPD) has chosen as the coating method since the simplicity of the making, relatively low cost, and the ability to coat things with complicated design. In this method, electrical current is used trough cathode and anode within the HA suspension. The electrical potential (voltage) will transport the small particle of HA to be deposited on the surface of TNTZ until producing an even layer of HA coating. This coating process requires two major parameters that are voltage and coating times. The desired quality of HA coating that would produce can be achieved by adjusting these parameters. Voltages are in the range of 7, 10, and 13 volts while coating times are in the range of 7, 10, and 13 minutes. Based on the result it is known that the best HA coating that can be produced are on 10 minutes and 10 volts. This best result shows the good surface morphology, optimum value of mass growth, coating thickness, and surface coverage. Based on this research it can be concluded that increasing voltage and coating times will increase the coating thickness and surface coverage of HA coating. This result shows that the EPD can be used to produce TNTZ titanium implant that coated with HA for orthopedic application.